Behavior of encased steel-high strength concrete columns against axial and cyclic loading. (April 2022) - Elbably, Ahmed; Ramadan, Osman; Akl, Adel; Zenhom, Naser
Abstract: There is limited information on the performance of encased steel-concrete (ESC) columns constructed of high-strength concrete. For instance, the analytical approach of Eurocode 4 applies only to columns made of normal weight concrete in the strength classes C20/25 to C50/60. As such, this paper presents an experimental investigation of the mechanical behavior of ESC columns made from normal strength (NS) concrete class C24/30 and high strength (HS) concrete class C56/70. The experiments comprise twelve ESC columns: four of which are axially loaded, while the other eight are subjected to axial load combined with lateral cyclic loads. The main design parameters investigated in the conducted experiments are concrete compressive strength, encased steel ratio, and axial (compression) load ratio. Relative effects of these parameters on strength enhancement, stiffness degradation, displacement ductility, and mode of failure are examined. Measured experimental results showed that ESC columns built of HS concrete failed abruptly with cracks passing through aggregates, whereas ESC columns made of NS concrete failed more gradually. For columns with encased steel ratios of 4% and 6%, the ESC columns made of HS concrete had ductility indices that are less than those made of NS concrete by up to 25% and 22%, respectively. Nevertheless, ESC columns built of HS concrete were able to withstand up to 24% more lateral loads than corresponding ESC columns made of NS concrete. Furthermore, increasing the axial load ratio resulted in an increase in the columns lateral load capacity accompanied by a loss in ductility and stiffness degeneration beyond the peak point. Highlights: Effect of applied axial load on the lateral strength of composite columns. Failure mode of composite columns made of high strength concrete. Performance of encased columns made of high strength concrete.